Chalcone Synthase (CHS) Gene Suppression in Flax Leads to Changes in Wall Synthesis and Sensing Genes, Cell Wall Chemistry and Stem Morphology Parameters - Zuk, Magdalena; Działo, Magdalena; Richter, Dorota; Dymińska, Lucyna; Matuła, Jan; Kotecki, Andrzej; Hanuza, Jerzy; Szopa, Jan (Frontiers in Plant Science, 2016)
The chalcone synthase (CHS) gene controls the first step in the flavonoid biosynthesis.In flax, CHS down-regulation resulted in tannin accumulation and reduction in lignin synthesis, but plant growth was not affected. This suggests that lignin content and thus cell wall characteristics might be modulated through CHS activity. This study investigated the possibility that CHS affects cell wall sensing as well as polymer content and arrangement. CHS-suppressed and thus lignin-reduced plants showed significant changes in expression of genes involved in both synthesis of components and cell wall sensing. This was accompanied by increased levels of cellulose and hemicellulose. CHS-reduced flax also showed significant changes in morphology and arrangement of the cell wall. The stem tissue layers were enlarged averagely twofold compared to the control, and the number of fiber cells more than doubled. The stem morphology changes were accompanied by reduction of the crystallinity index of the cell wall. CHS silencing induces a signal transduction cascade that leads to modification of plant metabolism in a wide range and thus cell wall structure.